Implementasi Pedagogik Kritis oleh Pendidik dan Sekolah Kristen di Indonesia Menurut Matius 9:35-36 - Sensius Amon Karlau; Ivo Sastri Rukua (UKI Press, 2023)
This research highlights the quality of education in Indonesia which is still far from expectations. Apparently, social problems and the uneven distribution of teachers in the 3T areas have exacerbated the quality of education nationally. The method used is qualitative with a literature study approach which is a literature review and text analysis. Interestingly, a critical pedagogical impression from a Christian perspective has been carried out, as found in the text of Matthew 9:35-36. Furthermore, critical pedagogy was realized simultaneously by Jesus in every city and village. So it is found that critical pedagogy in the Christian perspective is based on the divine compassion of Jesus. In fact, the sensitivity and attitude of Jesus' heart should influence the motivation of every Christian educator and educational institution. In line with that, every educator can empathize with the community in all situations and actual social problems. This is an important background for implementing critical pedagogy simultaneously and holistically to improve the quality of education that is evenly distributed throughout urban and rural areas, as Jesus did when teaching, preaching the Gospel and eliminating all diseases.